2020
DOI: 10.3233/jpd-191823
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson’s Disease in African Americans: A Review of the Current Literature

Abstract: Parkinson's disease (PD) is the second most common neurodegenerative disease, though evidence suggests that this disorder does not affect all racial groups similarly. Research in African Americans, in particular, has been conflicting. Some studies have found similar prevalence rates in African Americans and whites whereas other studies have found much lower prevalence and incidence rates in African Americans. A few studies identify potential factors underlying these discrepancies, including biologic difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 53 publications
0
32
0
Order By: Relevance
“…To best illustrate such unintended consequence, we offer two examples from neurology and cardiovascular medicine. Consider first epidemiological studies that have suggested individuals who self-reported as Black exhibited lower risk of Parkinson’s Disease (PD) compared with individuals who self-reported as White ( 31 33 ). More specifically, variants in MC1R that contribute to lighter pigmentation were associated with a nearly threefold greater risk of PD than those with MC1R variants that correspond to darker pigmentation ( 33 , 34 ).…”
Section: Racial Categorization Not Genetic Ancestrymentioning
confidence: 99%
“…To best illustrate such unintended consequence, we offer two examples from neurology and cardiovascular medicine. Consider first epidemiological studies that have suggested individuals who self-reported as Black exhibited lower risk of Parkinson’s Disease (PD) compared with individuals who self-reported as White ( 31 33 ). More specifically, variants in MC1R that contribute to lighter pigmentation were associated with a nearly threefold greater risk of PD than those with MC1R variants that correspond to darker pigmentation ( 33 , 34 ).…”
Section: Racial Categorization Not Genetic Ancestrymentioning
confidence: 99%
“…Black PD patients under-report motor impairment compared to White patients and therefore present later in the disease process, delaying their diagnosis and treatment. 25 Studies examining this phenomenon have demonstrated that Black patients are more likely to view PD as a part of normal aging and therefore may be less likely to act on their symptoms to seek treatment. 41 A large single-center study examining racial disparities in PD among 1159 patients showed greater disability and disease severity in Black patients.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies examining racial differences in incidence and prevalence of PD have demonstrated mixed findings. 25 Absent racial epidemiological differences, the persistent disparity that Black PD patients are five-fold less likely to undergo DBS relative to White patients is notable. It should also be noted that the disparities in the utilization of DBS are unfortunately not unique to DBS surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[21,17] Research also suggests that Black and Hispanic people are less likely to use health care services or self-report symptoms than White people, which may also contribute to underdiagnosis in these populations. [22,23,2] Healthcare Services Utilization Utilization was calculated for physician services (neurology -movement disorder specialist, general neurology, and primary care), therapy services (physical, occupational, and speech-language therapy), and mental health services (clinical psychology and psychiatry). Healthcare utilization was summarized as a function of age, sex, race and ethnicity, and rurality derived from data found in the Master Beneficiary Summary File.…”
Section: Prevalencementioning
confidence: 99%
“…[1] However, few studies have examined the health care utilization patterns of people living with PD on Medicare and how demographic differences, especially for groups that have been historically underrepresented in research, impact utilization of health care services. [2,3] Inconsistent symptom presentation and disease progression, as well as lack of biomarker or objective clinical diagnostic test to diagnose disease creates a challenge for diagnosing and treating PD, especially for physicians with less expertise in movement disorders. [4] As such, diagnosis and care is typically managed by general neurologists and/or movement disorder specialists in an outpatient setting.…”
Section: Introductionmentioning
confidence: 99%